A Short Review on the Development of Salt Tolerant Cultivars in Rice - Samiullah Khan; Muhammad Arshad Javed; Nusrat Jahan; Fazilah Abd Manan (International Journal of Public Health Science (IJPHS), 2016)
Rice is staple food for half of the world. With a population of almost 9.6 billion by the year 2050, there is a dire need of developing techniques to improve the crop plants, not only in terms of better yield but also to withstand harsh environmental conditions and stresses like drought, temperature, flood and salinity. Salinity is second to drought stress and hence it is very important to develop crops tolerant to salinity stress. This review discusses the mechanisms of salt tolerance and the recent developments in understanding the complex tolerance phenomena. One way to address the salinity issue is to develop tolerant rice varieties using conventional and modern breeding techniques for which screening the rice germplasm for the varieties with desired traits is critical. Conventional methods to develop tolerant rice varieties are discussed along with modern biotechnology techniques are also discussed. Quantitative Trait Loci (QTL) and Marker Assisted Selection (MAS) are promising techniques. In addition to these modern techniques, some recent developments in the fields of transgenic plants, haploid breeding and Somaclonal variations have also been discussed. The limited knowledge about molecular and genetic mechanisms to tolerate abiotic stresses, however is a barrier to efficiently develop tolerant cultivars. A combination of conventional and modern biotechnology techniques could possibly open up the new ways.